PENGARUH KUALITAS LAYANAN, KUALITS PRODUK, DAN PRESPSI HARGA TERHADAP KEPUASAAN KONSUMEN (Studi pada Dapoer Kerang Semarang) - Nurul Farida, 14.05.51.0267; Suteedjo, Bambang (Students' Journal of Economic and Management, 2018)
This study entitled the effect of service quality, product quality, perception of price and customer satisfaction on consumer Dapoer Kerang Semarang. The population in this study was customers in Dapoer Kerang Semarang. Sampling method used in this study was purposive sampling that technique determines the sample with particular consideration in accordance with the desired destination with the nomer of samples taken 100 respondents. The colleced data were analyze using factor analysis to test the validity of statement items, cronbach alpha of each partial independent variables were tested with the coefficient if determination and test fit the model to test and prove the influence of the partial each independent variable. The results of this study indicated that service quality, product quality, perception of price of customer satisfaction on consumerDapoer Kerang Semarang. Keyword: Service Quality, Corporate Image, Price of Perceptions and Costomer Satisfaction.